A rare solitary fibrous tumor in the ischiorectal fossa: a case report - Kazuhiko Morikawa; Shinsuke Takenaga; Koichi Masuda; Asami Kano; Takao Igarashi; Hiroya Ojiri; Kaoru Ueda; Mamoru Ishiyama; Nei Fukasawa (Surgical Case Reports, 2018)
Abstract Background A solitary fibrous tumor (SFT) is a rare mesenchymal tumor that occurs mostly in pleural sites, and an SFT occurring in the ischiorectal fossa is extremely rare. Because of the rarity, there are few reports detailing an SFT in the ischiorectal fossa. Case presentation A pararectal tumor was incidentally found in a 42-year-old man during a routine medical examination. The patient had no symptoms and no previous medical history. In the physical examination, a smooth-margined and hard elastic mass was felt, and in a digital rectal examination, the rectal mucosa appeared normal. A computed tomography (CT) scan showed a 5-cm, well-defined, solid mass in the left ischiorectal fossa. Contrast-enhanced CT in the early phase showed intense heterogeneous enhancement that persisted during the delayed phase. T2-weighted images of magnetic resonance imaging yielded heterogeneous intermediate and low signal intensity. Intense arterial enhancement suggested a hypervascular nature, and persistent delayed enhancement and low signal bands on T2-weighted images suggested a fibrous component of the mass. An SFT was suspected. Most SFTs are benign but have malignant potential. Our patient did not hope for surgery if the tumor was benign; therefore, an ultrasound-guided transperineal core needle biopsy was performed to decide on a treatment strategy. Microscopic examination showed tumor cells appearing as spindle and fibroblast-like cells within a collagenous stroma. Immunohistochemistry identified CD34 and vimentin, supporting the diagnosis of an SFT. The patient consented to excision of the mass. He was placed in a prone jackknife position, and the tumor was removed transperineally using a posterior approach (modified Kraske procedure). The levator ani muscle, external sphincter muscles, and rectum were not involved and separated from the tumor. The tumor was successfully resected en bloc with no complications. Five uneventful days post surgery, the patient was discharged. There was no local recurrence during the year following surgery. Conclusion Imaging findings reflect the tissue characterization such as hypervascularity and fibrous nature of SFTs. We have presented a rare case of an SFT in the ischiorectal fossa with useful imaging findings for diagnosis, treatment strategy, and successful surgical removal using a posterior approach.